Reconstructing the Iraqi Political System The Post-Saddam Era: The Role of the United States and the Coalition Forces - Abdul Wahed Jalal Nori (Universitas Muhammadiyah Yogyakarta, 2016)
The literature review about post-Saddam political system deals largely with the role of the United States and the coalition forces in establishingand stabilizing the country’s political system and its proper functioning. However, works referring to the institutions, processes and procedures of the political system are very few. There are occasional references toIraqi politics, but there are no many in-depth studies providing an analysis of the nature of the political system and its expected outcomes. The few works in the area do not differentiate between the three dominant ethnic groups and their concerns vis-à-vis the country’s internal organization and its future. Placing them in the same box as is often done is tantamountto equalizing centrifugal and centripetal forces, ignoring current history and obstructions created by colonial power.